Titanium clasp fabricated by selective laser melting, CNC milling, and conventional casting: a comparative in vitro study. Issue 1 (January 2019) - Tan, Fa-Bing; Song, Jin-Lin; Wang, Chao; Fan, Yu-Bo; Dai, Hong-Wei
Abstract: Purpose: This study aimed to investigate the effects of selective laser melting (SLM), milling methods, and casting on the behavior of titanium clasp. Methods: The clasp and its die simulating the molar were designed using 3D software. Clasp specimens were fabricated using SLM approaches (SLM Ti) and computerized numerical control (CNC) milling technology (Milling CPTi). Cast clasps of the same forms were also prepared as controls using titanium alloy powder (Cast Ti) and commercial pure titanium (Cast CPTi), following the conventional casting methods. The surface roughness and accuracy of clasps were analyzed. The changes in retentive force and permanent deformation were measured up to 10, 000 insertion/removal cycles. One-way analysis of variance and Tukey's test or Kruskal–Wallis H test were performed for data analysis and comparisons. Results: The Milling CPTi clasps had a smoother inner surface than the other groups ( p < 0.05). The accuracy of the inner surface showed no significant difference among the groups, whereas that of the outer surface showed significant differences ( p < 0.05). The SLM Ti clasp had significantly higher retentive forces than the other groups ( p < 0.05), but it rapidly reduced after 2000 insertion/removal cycles until the fracture of all specimens was at 4000 cycles. The Milling CPTi clasps had more permanent deformation, but the rate of reduction of retentive force was only 9.5% (at 10, 000 cycles). Conclusions: Milling has the potential to replace casting for fabricating removable partial denture (RPD) titanium clasps. However, SLM should be further improved for fabricating RPD titanium clasps before clinical application.